PENGARUH INTENSITAS MENONTON TAYANGAN PROGRAM ILOOK NET TV TERHADAP PERILAKU REMAJA DALAM BERBUSANA - Ayunita Nur Kamila; Layung Paramesti Martha; Imani Satriani (UNIVERSITAS PAKUAN, 2021)
This research is aimed to identify the effects of the intensity of watching the programs of iLook NET TV show on youth behavior in clothing. The purpose of this study is to find out how the intensity of watching the programs iLook shows teenagers in their attire in the school of SMK Negeri 3 Kota Bogor. This research uses X variables in watching intensity and Y variables in behavior. This study is using quantitative methods. The population of this research is sophomores XII SMK Negeri 3 Kota Bogor. This study included 92 people. The data collection techniques used in this study were mainly from questionnaires and observations. The technique used non probability sampling. The research agrees with thehypotheses on sthe study, it states that there is a influence between the intensity of the watch on teenagers behavior. Based on a test of relationship strength of 0,381, it can be said that the intensity of the relationship is judged to be very strong and comes out that the intensity of watching the iLook program has an influence on teenagers behavior by 0,145 while the rest (100% - 14,5% ) is 85,5 rated by another factor.